The Level of Morale Among Teachers of Learning Disabilities in English Language in Irbid, Jordan - Mohamad Ahmad Saleem Khasawneh (Newinera Publisher, 2021)
This study aimed at identifying the degree of morale among teachers of learning disabilities in English language in Irbid governorate from the teachers' point of view. The study used the descriptive approach and developed a questionnaire as an instrument of the study. The study sample included (30) male and female teachers. The questionnaire was administered to the sample after verifying its validity and reliability. The instrument's stability coefficient was (95%). The results of the study showed that the teachers' morale levels were moderate. The study recommended providing more training and incentives to teachers to boost their morale, which will have an impact on their performance